Deconstructing the Dissimilatory Sulfate Reduction Pathway: Isotope Fractionation of a Mutant Unable of Growth on Sulfate - Bertran, Emma; Leavitt, William D.; Pellerin, Andre; Zane, Grant M.; Wall, Judy D.; Halevy, Itay; Wing, Boswell A.; Johnston, David T. (Frontiers in Microbiology, 2018)
The sulfur isotope record provides key insight into the history of Earth’s redox conditions. A detailed understanding of the metabolisms driving this cycle, and specifically microbial sulfate reduction (MSR), is crucial for accurate paleoenvironmental reconstructions. This includes a precise knowledge of the step-specific sulfur isotope effects during MSR. In this study, we aim at resolving the cellular-level fractionation factor during dissimilatory sulfite reduction to sulfide within MSR, and use this measured isotope effect as a calibration to enhance our understanding of the biochemistry of sulfite reduction. For this, we merge measured isotope effects associated with dissimilatory sulfite reduction with a quantitative model that explicitly links net fractionation, reaction reversibility, and intracellular metabolite levels. The highly targeted experimental aspect of this study was possible by virtue of the availability of a deletion mutant strain of the model sulfate reducer Desulfovibrio vulgaris (strain Hildenborough), in which the sulfite reduction step is isolated from the rest of the metabolic pathway. When grown in open-system steady-state conditions at 10 % maximum growth rate, sulfur isotope fractionation factors averaged -15.9 per mil (1 sigma = 0.4), statistically indistinguishable from a pure enzyme study with dissimilatory sulfite reductase. We coupled these measurements with an understanding of stepspecific equilibrium and kinetic isotope effects, and furthered our mechanistic understanding of the biochemistry of sulfite uptake and ensuing reduction. Our metabolically informed isotope model identifies flavodoxin as the most likely electron carrier performing the transfer of electrons to DsrAB. This is in line with previous work on metabolic strategies adopted by sulfate reducers under different energy regimes, and has implications for our understanding of the plasticity of this metabolic pathway at the center of our interpretation of modern and palaeo-environmental records.